PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS XI PADA MATERI POKOK SISTEM KOLOID - Mardhika Surachman; Muntari -; Lalu Rudyat Telly Savalas (Postgraduate, University of Mataram, 2015)
The aims of this study were to: 1) generate interactive multimedia of colloidal system which is suitable to be implemented in schools, and to test the effectiveness of the interactive multimedia by: 2) knowing whether critical thinking skill of students who use context-based interactive multimedia is better than critical thinking skill of students who do not use context-based interactive multimedia on subject matter of the colloidal system. The method used in this study was research and development (R&D) according to the model of Borg & Gall’s development. The results of the expert validation by 4 validators and limited testing by 10 students showed that the interactive multimedia was very suitable to be used, with scores of 4.21 and 4.36 for expert validation and limited testing, respectively. Field trial using a non-equivalent control group design with 2 class samples, resulted in the critical thinking skill of probability value of 0.00 (p < 0.05). From this research we can conclude that: 1) context-based interactive multimedia can be developed by means of analyzing the materials in each sub materials as the basis for developing primary form of product, then tested for it’s feasibility, effectiveness, and revised through an expert validation, limited field testing, and main field testing, consecutively, so that the resulting product is considered to be suitable for learning process, and 3) critical thinking skill of students who use context-based interactive multimedia is better than critical thinking skill of students who do not use context-based interactive multimedia on the subject matter of the colloidal system. Keywords: interactive multimedia, context learning, concept mastery, critical thinking skill